GAMBARAN FUNGSIONAL TANGAN PADA GOJEK DI BANJARMASIN YANG MENGALAMI CARPAL TUNNEL SYNDROME - Warsana, Izra Ade; Hamzah, Arfian; Tahdi, Muhammad (Politeknik Unggulan Kalimantan, 2024)
Carpal Tunnel Syndrome is pain in the wrist caused by pressure on the median nerve when passing through the carpal tunnel in the wrist due to repeated injury or overuse, and is characterized by positive phalen and tinnel tests. This study aims to determine the functional picture of hands on gojek in Banjarmasin that experience carpal tunnel syndrome. This study used a type of quantitative research with an analytical descriptive research design to determine the functional of hands with carpal tunnel syndrome using phalen and tinnel tests. The results of the study obtained the most positive CTS at the age of 30-39 years (82,85%), male sex the most (90%), and based on the most functional hands category minimal disability (84,28%).